Analisis Problematika Pembelajaran Insya’ Arabi at-Tahriri Santri Kelas V (KMI) di Pondok Modern Gontor Dua - Dihyatun Masqon; Yoke Suryadarma; Achmad Farouq Abdullah (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2017)
Insha 'Arabi At-tahriri is one of the important subject in the Kulliyatul Mu'allimin Al-Islamiyah (KMI) curriculum. However, in the implementation, it was found that most of them (60%) still scored below 6. This study aims to find the problems that exist in the learning of Insya 'Arabi At-tahriri amongs student or santri of KMI, especially fifth grade student. This research is a field research using descriptive qualitative analysis. This research takes place in Modern Islamic Boarding School of Darussalam Gontor Campus 2. The sample of this research includes the Vice-director of KMI, teacher of KMI, staff of KMI, and all the fifth-grade students of KMI. The results of this study indicate the problem of learning Insya caused by several source. From the internal students, such as the lack of ability to express the language in writing competence, the weak mastery of Arabic Material and psychological aspect like willingness and motivation. And the external aspect of student including their activities outside class such as joining organization. While the factor of teachers, the problematic learning occurs due to teacher teaching method, some of them do not use student learning center method. It cause the teaching process becomes monotonous and bit boring.